2017
DOI: 10.1007/s11427-017-9121-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oxytetracycline production mediated via cooperation of resistance genes in Streptomyces rimosus

Abstract: Increasing the self-resistance levels of Streptomyces is an effective strategy to improve the production of antibiotics. To increase the oxytetracycline (OTC) production in Streptomyces rimosus, we investigated the cooperative effect of three co-overexpressing OTC resistance genes: one gene encodes a ribosomal protection protein (otrA) and the other two express efflux proteins (otrB and otrC). Results indicated that combinational overexpression of otrA, otrB, and otrC (MKABC) exerted a synergetic effect. OTC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Interestingly, in contrast to the 16S rRNA gene, the regulatory gene actII-orf4 was much more strongly expressed under the influence of otrA indicating a more specific function towards the natural product biosynthesis of our protein. Our results are in accordance with the results of Yin et al (2017), who reported that otrA over-expression rather than that of otrB and otrC in S. rimosus M4018 exhibits effects on OTC production. Surprisingly, overexpression of otrA in S. rimosus M527 had no effect on OTC production (data not shown), although it caused acceleration of morphological development (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, in contrast to the 16S rRNA gene, the regulatory gene actII-orf4 was much more strongly expressed under the influence of otrA indicating a more specific function towards the natural product biosynthesis of our protein. Our results are in accordance with the results of Yin et al (2017), who reported that otrA over-expression rather than that of otrB and otrC in S. rimosus M4018 exhibits effects on OTC production. Surprisingly, overexpression of otrA in S. rimosus M527 had no effect on OTC production (data not shown), although it caused acceleration of morphological development (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…OTRA confers OTC resistance by interacting with the ribosome and dislodging the bound OTC in a GTP-binding and hydrolysis-dependent manner (Mak et al, 2014). It has been described that the introduction of the otrA gene could enhance the host's resistance to OTC (Binnie et al, 1989;Doyle et al, 1991;Yin et al, 2017). In our study we showed that S. coelicolor M145-OA exhibited higher resistance to OTC than the control strain M145.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, it was observed that exogenous AP-3 at a concentration higher than 300 mg/L caused severe inhibition on the growth of WXR-24 ( Figure 1c and Table S2). Improving strain resistance has been widely used to enhance the yields of various antibiotics, such as oxytetracycline [28], doxorubicin [29], rimocidin [30], daptomycin [31] and toyocamycin [32]. However, these strategies mainly focus on overexpressing efflux genes or engineering resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been considerable interest in rational engineering of antibiotic producers. Improvement of antibiotic titers can be achieved by overexpression of key structural genes [ 69 ], resistance genes [ 70 ], ATP-binding cassette transporter genes [ 71 ] or amplification of the entire BGCs [ [72] , [73] , [74] , [75] , [76] ].…”
Section: Genetic Manipulation Of Regulators For Strain Improvementmentioning
confidence: 99%